Guaranteed Wages, Company Unemployment Benefits and the New Unemployment Insurance Act - Owen, C.F. (Relations industrielles / Industrial Relations, 1956)
SummaryThe purpose of this article is to continue the study of the factors involved in the possible co-ordination of unemployment insurance with the varied schemes entitled, "Guaranteed Wages", to amplify some of the issues that have been already raised, and to base the analysis on the new Unemployment Insurance Act, which came into operation in October, 1955. Also, special regard will be paid to the principle of the limited financial liability of the company involved in guaranteed wage proposals, and its possible implications for unemployment insurance.